The Role of Business in Achieving Millennium Development Goals through CSR (Corporate Social Responsibility) - Widiasari, Natalia; Iedarwati, Pradewi; Isololipu, Kurnianing (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2015)
owards the end of implementation period of Millennium Development Goals (MDGs), it is important to understand how far we have achieved it, what the best practice is and what has gone wrong. Looking at the achievement figure, it describes that we have not been far away from our starting point. Lack of power and ability are the main reasons. So it is time to look around. The country has many huge industries that have power and competency. The country has legal protection to ask the industries to cooperate, to coordinate and work together towards achieving MDGs. Industries, obligatory by law, and also some of them motivated by altruism must perform corporate social responsibility activities. This research describes the ongoing synergies that occurred in many ways in order to create better society and environment, which will lead to MDGs achievement.